KALIMAT NEGATIF DALAM LIRIK LAGU DI ALBUM NO.6 COLLABORATION PROJECT OLEH ED-SHEERAN - Gaol, Maria Esria Lumban; Pelealu, Hetty; Lasut, Theresia M.C (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â ABSTRACTÂ  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Maria Esria Lumban Gaol1Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â Dra. Theresia M. C. Lasut, M.Hum2Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Dra. Hetty Pelealu, S.H., M.Hum3Â  Â  Â  This research is entitled â€œNegative Sentences in the Song Lyrics in the album No.6 Collaboration Project by Ed-Sheeran.â€ The objectives of this research are to identify, classify and analyze forms of negative sentences and also to describe the functions and categories of someSong Lyrics. This research uses descriptive method. In analyzing the data, the writer used Aarts and Aarts (1982) and Thomson dan Martinet (1968: 107) theories and the data were taken from Ed-Sheeranâ€Ÿs song lyrics in album No.6 Collaboration Project (2019). The results of this research shows that there are 130 negative sentences found in song lyrics in album No.6 Collaboration Project (2019). The forms of negative sentences consist of negative sentences which are formed of the word not (49), negative sentences that contain periphrastic do (45), negative sentences with negative expression (36). Negative sentences formed of the word not that contains dare, need, and used, and negatif sentence with negative expression none, hardly and hardly ever, are not found in this research. TheFunctions found are Subject (Su), Predicator (P), Direct Object (DO), Adverbial (A), andcomplemen. Categories found are Noun Phrase (NP), Verb Phrase (VP), Adjective Phrase (Adj. P), and Prepositional Phrase (Prep. P).--------------------------------------------------Keywords: Negative Sentence, Descriptive Analysis, Functions and Categories, Album No.6 Collaboration Project (2019).